Education in dentistry in this “new normality” - Peña Soto, Claudio (2020)
The global crisis caused by the COVID-19 (SARS-CoV-2) pandemic has triggered a rethinking of the provision of educational services at all levels. Almost overnight, schools and universities around the world closed their doors, affecting 1.57 billion students in 191 countries.